Inheritance of soybean resistance to Corynespora cassiicola - Soares,Rafael Moreira (2020)
ABSTRACT The incidence of target spot, caused by Corynespora cassiicola, has gained increasing importance among the main soybean diseases in Brazil, and using susceptible cultivars can cause yield losses. Different susceptibility/resistance levels have been observed among cultivars in commercial crops but the genetics of the resistance to this pathogen is still unknown. To study the inheritance of soybean resistance to C. cassiicola, crosses were developed between cultivars including one cultivar resistant to target spot, BRS 316RR, one moderately resistant cultivar, BRS 184, and one susceptible cultivar BMX Potência RR. Parental generations, as well as F2 and F2:3 derived from their crosses, were evaluated as to severity and lesion size after inoculation with the pathogen. Quantitative analysis was applied to the data, and genetic models were adjusted for means and variances. Predominance of additive genetic effects controlling soybean resistance to C. cassiicola is suggested for the different crosses. The genetic models adjusted for the means detected an additive genetic effect more frequently. The additive variance D was detected only for the trait lesion size and had low heritability, indicating high environmental effect influencing the reaction. Based on mean and variance genetic models, further genetic gains are expected in the cross BRS 316RR x BMX Potência RR. The effect of genetic dominance was not important. The presence of significant epistasis in crosses between susceptible cultivars indicates the existence of at least two genes affecting resistance and that are interacting. The normal continuous distribution of the frequency of the number of individuals in different classes of resistance indicates that the resistance to C. cassiicola is quantitatively inherited and there is predominance of an additive genetic effect and low heritability.